2020
DOI: 10.3390/buildings10010008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Thermal Buoyancy in the Cavity of Ventilated Roofs

Abstract: Pitched wooden roofs are ventilated through an air cavity beneath the roofing in order to remove heat and moisture from the roof construction. The ventilation is driven by wind pressure and thermal buoyancy. This paper studies ventilation driven by thermal buoyancy in the air cavity of inclined roofs. The influence of air cavity design and roof inclination on the airflow is investigated. Laboratory measurements were carried out on an inclined full-scale roof model with an air cavity heated on one side in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The solar chimney consists of a solar collector that heats the air inside; this increase in temperature decreases its density so that it tends to rise, thus sucking air from inside the building to the outside, which in turn draws in outside air through the windows, as shown in the scheme of Figure 1. A great variety of works demonstrate the performance of natural ventilation and provide theoretical or experimental solar chimney system performance results; however, there are few works on the integration of these systems into the total or partial volume of a housing model [26][27][28][29][30][31].…”
Section: Solar Chimneymentioning
confidence: 99%
“…The solar chimney consists of a solar collector that heats the air inside; this increase in temperature decreases its density so that it tends to rise, thus sucking air from inside the building to the outside, which in turn draws in outside air through the windows, as shown in the scheme of Figure 1. A great variety of works demonstrate the performance of natural ventilation and provide theoretical or experimental solar chimney system performance results; however, there are few works on the integration of these systems into the total or partial volume of a housing model [26][27][28][29][30][31].…”
Section: Solar Chimneymentioning
confidence: 99%
“…Bunkholt et al [48] investigated, through a laboratory study, how the air flow through a ventilated roof cavity is affected by temperature and air cavity design. Measurements indicated that the air cavity temperature and flow conditions were affected by the cavity width as well as the roof angle.…”
Section: Roofsmentioning
confidence: 99%
“…The experimental study was performed at one of the laboratories of SINTEF and NTNU in Trondheim, Norway (Bunkholt, 2019;Bunkholt et al, 2020;Svantesson and Sa¨we´n, 2019). Experiments were conducted on a full-scale model of a section of a cavity-ventilated roof construction, represented schematically in Figure 6.…”
Section: Experimental Studymentioning
confidence: 99%